Phytochemical Analysis and Anti-Thrombocytopenic Activity of Dayak Onion (Eleutherine palmifolia (L.) Merr) Extract and Fractions with HR-LCMS Profiling of Active Compounds - Apriliana, Anita; Milanda, Tiana; Susilawati, Yasmiwar; Wilar, Gofarana (Universitas Gadjah Mada, 2026)
Thrombocytopenia, characterized by a low platelet count, poses significant clinical challenges and can arise from various etiologies. This study investigates the anti-thrombocytopenic effects of Dayak onion (Eleutherine palmifolia (L.) Merr) extracts and their fractions in Wistar rats. Ethanolic extracts and fractions were evaluated for their efficacy in enhancing platelet production. Male Wistar rats were administered doses of 100, 200, and 300 mg/kg, and platelet counts were measured at 24, 48, and 72 h post-treatment. Results indicated that all doses of the ethanolic extract significantly increased platelet counts over time, with the ethyl acetate fraction demonstrating the highest efficacy at a dose of 24.087 mg/kg, achieving significant increases as early as 24 h post-administration. Phytochemical analysis revealed substantial levels of phenolics (318.80 mg GAE/g) and flavonoids (45.63 mg QE/g) in the ethyl acetate fraction, with quercetin identified as a prominent compound via HR-LCMS. These findings suggest that Dayak onion possesses promising anti-thrombocytopenic properties, warranting further exploration as a therapeutic agent for accelerating platelet recovery in conditions such as dengue fever.